Analysis of the Suitability of Pasumpahan Island Marine Tourism Based on the Tourism Suitability Index - Muhammad Aditya Pradana; Rifardi Rifardi; Syahril Nedi (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Pasumpahan Island is one of the national and international tourist destinations located in Padang City, West Sumatra Province. This island is included in the Regional Marine Protected Area (KKLD) which has a very good coral reef ecosystem, so its management must be following applicable laws and regulations. This research was conducted in March 2022 on Pasumpahan Island, Bungus District, Padang City, West Sumatra Province. The method used is a field survey with data collection using a purposive sampling method. The measured index of water quality was processed using the Storet method. Pasumpahan Island's physical environment is relatively good with a wide expanse of white sand. The suitability of marine tourism in this island area based on the tourism suitability index (IKW) is 85.71% which is included in the S1 category (very suitable). The water quality of the Pasumpahan Island tourist area based on the water quality index (IKP) is in the very good category. Based on the IKW and IKP, the tourist area of Pasumpahan Island is very feasible to be developed as a national marine tourism area